Static optimization design of a printer heat-roller based on sensitivity analysis. Issue 1 (January 2020) - Wen, Guang; Liu, Pingping; Zuo, Fangjun; Su, Rui; Jia, Meiwei; Li, Gangjun
Abstract: Taking the printer heat-roller as the research object, the static characteristics and sensitivity were analyzed by finite element method. Through static analysis, the static characteristics of the heat-roller under working load were obtained, and the size parameters which have great influence on the static characteristics of the structure were determined by sensitivity analysis. The heat-roller was optimized to reduce the self-weight of the structure. It is concluded that the maximum working stress of heat-roller under working load is less than the allowable stress of material, and the structural dimension meets the strength requirement. According to the sensitivity analysis results, it can be seen that the structural parameters which have great influence on the static characteristics of the heat-roller are d 3, d 1, l 1, l 2 and F . Through optimum design, the weight of the roller was reduced by 15.18%. The analysis results provide a reference for the design of other similar structures.